Nutritional status and survival of 8247 cancer patients with or without diabetes mellitus—results from a prospective cohort study. (19th August 2020) - Cong, Minghua; Zhu, Wenjie; Wang, Chang; Fu, Zhenming; Song, Chunhua; Dai, Zhong; Yao, Keqing; Guo, Zengqing; Lin, Yuan; Shi, Yingying; Hu, Wen; Ba, Yi; et al.
Abstract: Background: The number of cancer patients with diabetes mellitus (DM) is steadily rising. Little is known about the nutritional status of this population. This study characterized the nutritional status and survival of cancer patients with diabetes compared with those without diabetes. Methods: A total of 8247 cancer patients were prospectively enrolled from 72 hospitals in China and followed until August 2019. A global estimation of the nutritional status was performed for each participant using standardized tools. The outcomes were cancer‐specific survival (CSS) and overall survival (OS). Results: The incidence of diabetes was 7.6% in the whole population. In comparison with the non‐DM group, the DM group had greater body weight, but a similar fat‐free mass, a lower handgrip strength and a decreased Karnofsky performance score. A higher proportion of patients with diabetes were overweight/obese as indicated by BMI. The percentage of patients who were at risk of malnutrition (evaluated by PG‐SGA) was higher in the DM group (score ≥ 4, 56.7% vs 52.9%). Patients with DM showed a worse CSS (4‐year CSS, 62% vs 73%) and OS (4‐year OS 39% vs 52%). Diabetes was associated with an increased risk of both cancer‐specific (hazard ratio (HR) = 1.282, 95% confidence interval (CI) 1.070‐1.536) and overall (HR = 1.206, 95% CI 1.040‐1.399) mortality. Conclusions: Cancer patients with diabetes had a larger body mass but lower muscle strength, poorer performance status and higher incidence of malnourishment. Diabetes was associated with compromised survival. Tailored nutritional intervention is necessary for this subpopulation of patients. Abstract : In this large prospective cohort study, cancer patients with diabetes were found to have bigger body mass yet lower muscle strength, poorer performance status and higher incidence of malnourishment. Complication with diabetes independently predicted compromised survival among cancer patients.